2004
DOI: 10.1200/jco.2004.12.108
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Treatment in Conservative Management of Operable Breast Cancer: Dissection or Radiotherapy? Results of a Randomized Study With 15 Years of Follow-Up

Abstract: In early breast cancers with clinically uninvolved lymph nodes, our findings show that long-term survival does not differ after axillary radiotherapy and axillary dissection. The only difference is a better axillary control in the group with axillary dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
120
0
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(136 citation statements)
references
References 15 publications
4
120
0
8
Order By: Relevance
“…There is some evidence to support the management of women who are clinically node negative with axillary radiotherapy only. A study with 15 years of follow-up has found no difference in survival between clinically node negative women with early breast cancer managed with ALND or axillary radiotherapy, although a slightly higher rate of axillary recurrence was noted [72]. However this may be an equitable solution, in view of the fact that MM are likely to represent a lower risk of local and distant failure than macrometastasis and women could be spared the morbidity of ALND.…”
Section: Discussionmentioning
confidence: 93%
“…There is some evidence to support the management of women who are clinically node negative with axillary radiotherapy only. A study with 15 years of follow-up has found no difference in survival between clinically node negative women with early breast cancer managed with ALND or axillary radiotherapy, although a slightly higher rate of axillary recurrence was noted [72]. However this may be an equitable solution, in view of the fact that MM are likely to represent a lower risk of local and distant failure than macrometastasis and women could be spared the morbidity of ALND.…”
Section: Discussionmentioning
confidence: 93%
“…In SLND studies, including the current study, the axillary lymph node recurrence rate after SLND is comparable to or less than the axillary lymph node recurrence rate of 1-2.5% after ALND for early-stage breast carcinoma at a median interval of 2.6 years between axillary surgery and disease recurrence. [17][18][19][20] The prevalence of axillary metastases is highly variable in patients with clinically negative lymph nodes and can be predicted based on the primary tumor size, ranging from 12.3% for T1a tumors, 18.5% for T1b tumors, 30.4% for T1c tumors, 48% for T2 tumors to 77.3% for T3 tumors. 21 The risk of axillary lymph node recurrence also varies accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…106 In these patients, excision of all regional lymph nodes from the axilla compared with excision of sentinel lymph node alone did not result in additional benefit. 107,108 Therefore, it was concluded that removal of the sentinel lymph node might be sufficient and more extensive removal of axillary nodes was not recommended in patients without sentinel lymph node metastasis.…”
Section: The Role Of Vegfs In Lymphangiogenesismentioning
confidence: 99%